2016
DOI: 10.1371/journal.pone.0147015
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Size and Function in a Canine Model of Chronic Atrial Fibrillation and Heart Failure

Abstract: BackgroundOur aim was to assess how atrial fibrillation (AF) induction, chronicity, and RR interval irregularity affect left atrial (LA) function and size in the setting of underlying heart failure (HF), and to determine whether AF effects can be mitigated by vagal nerve stimulation (VNS).MethodsHF was induced by 4-weeks of rapid ventricular pacing in 24 dogs. Subsequently, AF was induced and maintained by atrial pacing at 600 bpm. Dogs were randomized into control (n = 9) and VNS (n = 15) groups. In the VNS g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
5
1
1
Order By: Relevance
“…Our study revealed that CMR-FT LA strain could identify subtle LA booster pump dysfunction undetectable by conventional active LAEF. Our study found no correlation between the LA strain/strain rate and heart rate, as a conflicting result to a previous study reported by Goldberg et al in which a curvilinear increase in the LA strain with a longer RR interval ( r = 0.45, P < 0.0001) was found 32 . In our cohort, 90 out of 106 PAF patients (84%) took antiarrhythmic drugs with negative inotropic effects and more than half of them (56%) were prescribed beta-blockers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that CMR-FT LA strain could identify subtle LA booster pump dysfunction undetectable by conventional active LAEF. Our study found no correlation between the LA strain/strain rate and heart rate, as a conflicting result to a previous study reported by Goldberg et al in which a curvilinear increase in the LA strain with a longer RR interval ( r = 0.45, P < 0.0001) was found 32 . In our cohort, 90 out of 106 PAF patients (84%) took antiarrhythmic drugs with negative inotropic effects and more than half of them (56%) were prescribed beta-blockers.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, the high proportion of negative inotropic medicine (mainly betablockers) use with various types and doses may have resulted in a loss of the entire correlation between the LA strain and heart rate in this study. Additionally, the correlation between the LA strain and heart rate was established in normal conditions in the previous studies 32 , 34 . The difference in the LA between normal and PAF patients (LA functional and anatomical remodeling) may lead to conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, STE‐derived PALS, PACS, and CSI were all univariate predictors of survival. Left atrial strain recently has been studied to validate the technique in clinically healthy dogs and to evaluate strain changes in dogs under experimental conditions, or in dogs with naturally occurring MMVD . With progression of disease, STE‐derived variables tend to decrease as a consequence of progressive impairment in LA contraction and relaxation .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there are different approaches to its computer simulation that are validated with real data. Apart from human cellular models, sheep [36][37][38][39][40][41][42], canine [43][44][45][46][47], frog [48], rabbit [49], and mice [50] models have also been discussed in the literature.…”
Section: Cellular Modelingmentioning
confidence: 99%